Both sides of the camera: anthropology and video in the study of a Gcaleka women's rite called Intonjane. - Cloete, Laura (My University, 2015)
This thesis explores the potential of video as a research tool for anthropologists in the recording of a single ritual. The study examines interactions between ethnographers, informants and viewers. The thesis reveals the capacity of video to make possible close, detailed readings of performance in terms not originally anticipated by the researcher. Archival storage of the video recording allows for critique and assessment of the research. The case study chosen in which to test the potential of \ dcso as a research tool was a woman's 'initiation' r^L'ial (called inton jane) in Shixini in the Eastern Gape (in what was, until recently, the independent homeland of Transkei). Historically, the ritual was supposedly held at the time of a girl's first menstruation, this being the physical symbol of her transformation into adulthood. Ritual seclusion served to effect an accompanying social transformation in preparation for marriage. Paradoxically, in the late 1980's, it was older women and mothers, already married and well past the age of first menstruation, who were undergoing the ritual seclusion and symbolic marriage. The study explores this paradox with the goal of understanding the purpose of the ritual in contemporary times. By recording large segments of the ritual on video, and subjecting the footage to a close analysis of verbal and non-verbal aspects of performance, both the ritual and the merits of video as a research tool could be examined. Video was utilised, in an interactive research process, as an information elicitation tool. The analysis of the recorded text of the ritual brings to the fore elements which make what is apparently a paradox understandable. The elements which explicate the paradox were not anticipated when the research commenced, and in all likelihood would have eluded a researcher who did not have the benefit of the incidental capture on video. The thesis reveals the enormous Contribution video can make to research and suggests that video has an important contribution to make to the discipline of anthropology.
Keywords: Ethnology--South Africa--Eastern Cape; Xhosa (African people)--Rites and ceremonies; Rites and ceremonies--South Africa--Eastern Cape; Women--Health and hygiene--South Africa--Eastern Cape--Sociological aspects; Women--Health and hygiene--South Africa--Eastern Cape--Sociological aspects; Video recordings--Production and direction--South Africa--Eastern Cape.; Visual anthropology--South Africa--Eastern Cape; Motion pictures in ethnology--South Africa--Eastern Cape